Paradigma Penerapan Asas No Work No Pay dalam Penentuan Upah Proses - Syahwal - Syahwal (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The principle of no work no pay is a legal principle in labor law whose content shows the relationship between wages and work in an employment relationship. That means workers will not get paid if they do not work. The legal principle is frequently applied by courts in determining wages for workers whose employment relationship have been terminated so that workers lose their rights to process wages. With a non-doctrinal study that uses court decisions, this research examines the legal considerations of the panel of judges in applying the principle of no work no pay when determining whether to give wages to workers whose employment relationship has been terminated. The study showed that the paradigm of applying the no work no pay principle is still focused on the positivist mindset, which is deeply rooted in court as well as in the process of legal reasoning by the panel of judges. So that workers who do not work are considered as a single legal fact without other legal facts that accompany it.